THE EFFECTS OF DIFFERENT LEVELS OF DIETARY FISH OIL, SOYBEAN OIL, AND SUNFLOWER OIL ON PERFORMANCE AND IMMUNITY RELATED PARAMETERS OF BROILER CHICKEN - W. Liu1; R. Pedram; F. Javandel; S. Nasabian; Alireza Seidavi2 (Journal of Animal and Plant Sciences, 2017)
The study was designed to investigate the effects of different levels of dietary oil additives on the feeding performance and immunity related parameters of broiler chicken. In total, two hundred and eighty (280) day-old male broiler chicks (Ross 308) were randomly placed in 28 cages with dimensions of 1.0 × 1.0 meters based on a completely random design. There were two levels (1.0% vs. 2.0%) of additive soybean oil, sunflower oil, and fish oil with uniform vaccination programs and feed ingredients and nutrient treatments in the trials. The experimental results showed that there were no differences among the body weight indexes of broiler chicken (42nd day of age), while there were significant differences among the feed conversion ratio and feed intake indexes of these broiler chicken (from 1st to 42nd days of age). Particularly, the broiler chicken fed with 2.0% sunflower oil in diet had more significant lower performance indexes of feed conversion ratio and feed intake than the control and other dietary oil treatment panels (1.0% and 2.0%). Furthermore, all the dietary additives of two levels (1.0% and 2.0%) of fish oil, soybean oil, and sunflower oil brought about significant different immunity indexes of broiler chicken (42nd day of age). In conclusion, these results suggested that different dietary supplementation levels (especially high levels) of dietary oil additives can promote the feeding performance and alter immunity parameters of broiler chicken.
Keywords: Feed Efficiency; Broiler Chick; Thymus; Humoral Antibody; Immune